2004
DOI: 10.1097/01.paf.0000136639.69128.bc
|View full text |Cite
|
Sign up to set email alerts
|

Weight Force During Prone Restraint and Respiratory Function

Abstract: Prone maximal restraint position (PMRP, also known as hogtie or hobble) is often used by law enforcement and prehospital personnel on violent combative individuals in the field setting. Weight force is often applied to the restrained individual's back and torso during the restraint process. We sought to determine the effect of 25 and 50 lbs weight force on respiratory function in human subject volunteers placed in the PMRP. We performed a randomized, cross-over, controlled trial on 10 subjects placed in 4 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 18 publications
3
64
0
Order By: Relevance
“…30,44 Reports of sudden death in individuals while in this position have been reported in the medical literature for the past few decades, which has created some controversy regarding its safety. 30,36,45 It has been hypothesized that the PMRP prevents adequate chest and abdominal movement and places the individual at risk for asphyxiation. 36,41,42 The result of these deaths are likely multifactorial, with many factors difficult or impossible to replicate or measure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30,44 Reports of sudden death in individuals while in this position have been reported in the medical literature for the past few decades, which has created some controversy regarding its safety. 30,36,45 It has been hypothesized that the PMRP prevents adequate chest and abdominal movement and places the individual at risk for asphyxiation. 36,41,42 The result of these deaths are likely multifactorial, with many factors difficult or impossible to replicate or measure.…”
Section: Discussionmentioning
confidence: 99%
“…33 Two additional studies of healthy subjects focused on ventilator measures while in the PMRP with progressive weight increases on the subjects back also reported similar results. 30,46 One of the more recently researched associations with custody deaths is ExDS. Despite the relatively low incidence of ExDS, the syndrome has been reported to have a high fatality rate and is often associated with the use of illicit drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of 21 cases of death associated with excited delirium, 86 all of the subjects had undergone restraint. Chan et al 87 concluded that such a position resulted in a ''restrictive pulmonary function pattern," but with no evidence of hypoxia (i.e., no O 2 saturation less than 96%). This conclusion was based upon observations of normal subjects (not exhibiting excited delirium).…”
Section: Confounding Factors That May Be Present During Ecd Applicatimentioning
confidence: 99%